Measurement report: Diurnal variations of brown carbon during two distinct seasons in a megacity in northeast China - Y. Cheng; X. Cao; J. Liu; Y. Zhong; Q. Yu; Q. Zhang; K. He (Atmospheric Chemistry and Physics, 2023)
Brown carbon (BrC) represents an important target for the “win-win” strategy of mitigating climate change and improving air quality. However, estimating co-benefits of BrC control remains difficult for China, partially because current measurement results are insufficient to represent the highly variable emission sources and meteorological conditions across different regions. In this study, we investigated, for the first time, the diurnal variations of BrC during two distinct seasons in a megacity in northeast China. The winter campaign conducted in January 2021 was characterized by low temperatures rarely seen in other Chinese megacities (down to about −20 ∘C). The mass absorption efficiencies of BrC at 365 nm (MAE365) were found to be ∼ 10 % higher at night. The variations of MAE365 could not be explained by the influence of residential biomass burning emissions or secondary aerosol formation but were strongly associated with the changes of a diagnostic ratio for the relative importance of coal combustion and vehicle emissions (RS/N<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="24pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="9bc8a6f318a29345d11c60fbb2f6b18a"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-23-6241-2023-ie00001.svg" width="24pt" height="14pt" src="acp-23-6241-2023-ie00001.png"/></svg:svg>). Given that most coal combustion activities were uninterruptible, the higher nighttime MAE365 in winter were attributed primarily to increased emissions from heavy-duty diesel trucks. The spring campaign conducted in April 2021 was characterized by frequent occurrences of agricultural fires, as supported by the intensive fire hotspots detected around Harbin and the more-than-doubled ratios of levoglucosan to organic carbon (LG/OC<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="39pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="9ac2b56dc932abb12a017bd764326d5a"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-23-6241-2023-ie00002.svg" width="39pt" height="14pt" src="acp-23-6241-2023-ie00002.png"/></svg:svg>) compared to the winter campaign. In spring, the MAE365 depended little on RS/N<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="24pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="9729f6d9d958f2207ff42093b6c59c18"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-23-6241-2023-ie00003.svg" width="24pt" height="14pt" src="acp-23-6241-2023-ie00003.png"/></svg:svg> but exhibited a strong positive correlation with LG/OC<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="39pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="2ecd6920e4a713999000b7f89a205d37"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-23-6241-2023-ie00004.svg" width="39pt" height="14pt" src="acp-23-6241-2023-ie00004.png"/></svg:svg>, suggesting open burning emissions as the dominant influencing factor for BrC's light absorption capacity. MAE365 were ∼ 70 % higher at night for the spring campaign, pointing to the prevalence of nighttime agricultural fires, which were presumably in response to local bans on open burning. It is noteworthy that the agricultural-fire emissions resulted in a distinct peak at ∼ 365 nm for the light absorption spectra of BrC, and candidates for the compounds at play were inferred to be aromatic species with nitro-functional groups. The presence of the ∼ 365 nm peak complicated the determination of absorption Ångström exponents for the agricultural-fire-impacted samples. In addition, the ∼ 365 nm peak became much less significant during the day, likely due to photobleaching of the relevant chromophores.